Effects of Technological Treatments of Dietary Palm Kernel Meal on Feed Intake, Growth and Body Composition of Oreochromis Niloticus Reared in Concrete Tanks - Adjanke, Amakoe; TONA, Kokou; TOKO, Ibrahim IMOROU; GBEASSOR, Messanvi (The International Journal of Biotechnology, 2018)
An experiment was conducted to determine the effect of treated palm kernel meal in diets on production parameters of Nile tilapia Oreochromis niloticus reared in concrete tanks. Fingerlings of Tilapia with an average initial weight 6.22 ± 0.25 g and an average size 7.58 ± 0.21 cm were fed four isonitrogenous diets each containing 30% palm kernel meal treated one-hour or not. So we have NT (untreated), DW (dipped in water), CW (cooked in water) and SW (steamed). These diets were compared with a commercial fish feed, Raanan (RA), all about 32% crude protein. After 8 weeks of experiment the final body weight varied between 29.57 and 43.01 g according to the tested treatments. The best growth rate and food conversion ratio were obtained with diet CW containing palm kernel meal cooked in water with specific growth rate (SGR) of 3.24 %/d and food conversion ratio (FCR) of 1.97 against a SGR of 3.44%/d and a FCR of 1.72 obtained with commercial feed (RA). Moreover, the tested diets do not seem to have any effect on the intestine size but the cooking seems to act on fish liver weight and body composition. The production parameters were improved with the diet containing palm kernel meal cooked in water which seems to be the interest food for O. niloticus on growing.